2002
DOI: 10.1093/milmed/167.11.877
|View full text |Cite
|
Sign up to set email alerts
|

Work Stress in the Military: Prevalence, Causes, and Relationship to Emotional Health

Abstract: Authors alone are responsible for opinions expressed in the contribution and for its clearance through their federal health agency, if required.NUMBER 11 MILITARY MEDICINE, 167, 11:877,2002 Work fering from significant work stress, 15% reported that work stress was causing them significant emotional distress, and 8% reported experiencing work stress that was severe enough to be damaging their emotional health. Generic work stressors were endorsed more frequently than military-specific stressors. Conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 10 publications
3
50
0
5
Order By: Relevance
“…Similarly depression in navy recruits has been linked to loneliness, higher levels of stress, more life change units, lower sense of belonging, emotion oriented coping and less task oriented coping [5]. A recent study [6], has reported that military personnel have higher job stress than their civilian counterparts. 26% of the service men reported significant work stress, 15% reported that work stress led to emotional distress and 8% claimed that work stress was severe enough to affect their emotional health.…”
Section: Original Articlementioning
confidence: 99%
“…Similarly depression in navy recruits has been linked to loneliness, higher levels of stress, more life change units, lower sense of belonging, emotion oriented coping and less task oriented coping [5]. A recent study [6], has reported that military personnel have higher job stress than their civilian counterparts. 26% of the service men reported significant work stress, 15% reported that work stress led to emotional distress and 8% claimed that work stress was severe enough to affect their emotional health.…”
Section: Original Articlementioning
confidence: 99%
“…Studies have shown that stress in the military is caused by a myriad of problems common to the civilian sector rather than military-specific stressors such as deployments Pflanz & Sonnek, 2002). In addition research conducted by Etzion and colleagues (1998) showed that reserve service, which has many similarities to active duty deployments, resulted in a decrease in job stress and burnout when the reservists returned to their civilian jobs.…”
Section: Burnoutmentioning
confidence: 99%
“…Indeed, the deployees showed significant decreases in both emotional exhaustion and burnout when they returned to their homestation job from a deployment. Therefore, the strains of emotional exhaustion and burnout within the military are not likely to be a result of military specific stressors such as a deployment, but more than likely a result of problems common to the civilian sector such as work overload, role conflict, and role ambiguity (Pflanz & Sonnek, 2002).…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Con personal activo, igualmente, se han realizado varios estudios que abordan diferentes aspectos de la salud del personal militar tales como trastornos psiquiátricos (12,23), mortalidad por lesiones (24), estrés ocupacional (25,26), salud mental (27)(28)(29)(30)(31)(32) Un aspecto importante menos mencionado o mencionado indirectamente en los estudios americanos e ingleses es el de la calidad de vida. El concepto de calidad de vida se ha estudiado desde una perspectiva biomédica, psicológica y social, y se ha definido, principalmente desde un punto subjetivo, como la percepción de las personas sobre diversos ámbitos de sus vidas, destacando la relevancia del contexto social, cultural y del sistema de valores en el que experimentan su vida cotidiana (41).…”
Section: Introductionunclassified